Study of Stress Annealing Effect on Giant Magneto-impedance of Fe-based Ribbons. Issue 1 (16th January 2016) - Jianya, Ge; Xiaohong, Yang; Shenggang, Wang; Jing, Zhao; Ming, Cheng; Xingwei, He; Yunzhang, Fang; Fangye, Shi
Abstract : Fe-based nanocrystalline ribbons were successfully prepared. The giant magneto-impedance (GMI) effect that was found in these studies could be effectively increased by temperature annealing together with stress annealing. After applying a certain stress, the same GMI effect can be obtained with a much lower annealing temperature. In the present paper, it was found that the crystallization of Fe-based sample can reach its best GMI effect with a ratio of ΔZ to Z at 1141% at 500 °C annealing and 53 MPa.